Psicomotricidad y su influencia en la metodología del aprendizaje en los niños de educación inicial - Carpio Zúñiga, Karem Maylin (2024)
In the present research we considered analyzing the influence of psychomotricity in the learning methodology of children in early childhood education at the "Adolfo María Astudillo" Educational Unit in Babahoyo, Los Ríos province. The main objective was to understand how psychomotricity impacts on the educational methodology of early education students. A mixed approach methodology was used with both qualitative and quantitative aspects based on bibliographic data from scientific articles, masters, magazines, books, internet pages and the acquisition of important data to be able to carry out surveys directed to students and parents. The results showed a variety of opinions about psychomotor skills among each of the participants, from an acceptable amount of knowledge to a significant percentage with low knowledge of the subject. The need to promote improvements in the understanding of these techniques to support children at home and in the educational environment was highlighted. As the most noteworthy conclusions, it was emphasized that the educational institution should implement psychomotor stimulation programs that address genetic, environmental and developmental factors. These programs could include activities designed to improve gross and fine motor skills, coordination and balance.